Sekolah Sampah Bantala Abyudaya Sebagai Upaya Mitigasi Permasalahan Sampah Di Kalurahan Sendangsari, Pengasih Kulon Progo: - - Winarno, Joko; Yoga, Alan Prima; Zahra, Nafisa Ananda; Faradila, Niza; Simbolon, Yohana Cristine; Manggala, Habib Eky; Ambarwati, Anisa Fitriana; Al Faruq, Tsabit Faiz; Setyaningsih, Emy (LPPM IST AKPRIND Yogyakarta, 2024)
Environmental education, mainly focusing on waste management, can increase public awareness and ability to help reduce the impacts caused by environmental changes. One way to overcome this problem is to establish a Waste School. Therefore, the PPK Ormawa Team of BEM AKPRIND University, in collaboration with Proklim Bandala Abyudaya located in Sendangsari Pengasih Kulon Progo Village, established a Waste School named Sekolah Sampah Bantala Abyudaya (Kolah Banyu). The purpose of establishing Kolah Banyu is to provide education on environmental conservation and waste management and to be a place where students and the general public can try waste management methods such as recycling, composting, and other methods. The method used to establish Kolah Banyu consists of four stages: 1) Preparation; 2) Coordination meeting; 3) Assistance in preparing the management of the Waste School; 4) Proposal for the establishment of Kolah Banyu, and 5) Approval of the Kolah Banyu institution. The issuance of the Kolah Banyu institutional decree and the inauguration of the management by the Sendangsari Village Head was the beginning of the operation of Kolah Banyu. The establishment of Kolah Banyu also received extraordinary support from the Kulon Progo Environmental Service, the Head of Sendangsari Village, and Kampung Berseri Astra (KBA), which was formed by Astra Indonesia, which is committed to continuing to accompany Kolah Banyu in realizing its vision and mission.